2005
DOI: 10.1103/physrevlett.95.076103
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of a Thin Silica Film on a Mo(112) Substrate: A Two-Dimensional Network ofSiO4Tetrahedra

Abstract: The structure of a thin single crystalline SiO(2) film grown on Mo(112) has been studied by scanning tunneling microscopy, infrared reflection absorption spectroscopy, and x-ray photoelectron spectroscopy. In excellent agreement with the experimental results, density functional theory calculations show that the film consists of a two-dimensional network of corner sharing [SiO(4)] tetrahedra, with one oxygen of each tetrahedron binding to the protruding Mo atoms of the Mo(112) surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
191
0
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(213 citation statements)
references
References 23 publications
13
191
0
9
Order By: Relevance
“…Furthermore, at certain tunneling parameters the Si atoms could be imaged (Fig 2b) and, again, this fact has been proven by comparing the experimental and simulated STM images [32,36]. [36] showed that isolated [SiO 4 ] clusters must appear in STM as large single spots (see Fig.…”
Section: Scanning Tunneling Microscopy (Stm)mentioning
confidence: 82%
See 3 more Smart Citations
“…Furthermore, at certain tunneling parameters the Si atoms could be imaged (Fig 2b) and, again, this fact has been proven by comparing the experimental and simulated STM images [32,36]. [36] showed that isolated [SiO 4 ] clusters must appear in STM as large single spots (see Fig.…”
Section: Scanning Tunneling Microscopy (Stm)mentioning
confidence: 82%
“…Further XPS studies have verified formation of two different O species in the "Opoor" silica films [32,36]. Two overlapping signals centered at ~532.5 and ~531.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 The system consists of an ultra-thin silicon-dioxide film that is prepared on a Mo(112) surface. 6,7,8 The fundamental building blocks of the oxide layer are six-membered -Si-O-rings, enclosing a hole of 3-4 Å diameter. These openings provide access to nano-pores located at the Mo-silica interface, which offer an attractive binding environment for metal atoms and small molecules.…”
Section: Introductionmentioning
confidence: 99%